Analisis Penanganan Anak Putus Sekolah Di Kampung Nelayan Kecamatan Medan Belawan Kota Medan - Fauzhan Azhima; Beby Masitho Batubara; Nina Angelia (Universitas Medan Area, 2022)
This research was conducted with the aim of knowing the factors causing and handling school dropouts in the Medan Belawan Fisherman Village. Where in this village about 80% of children drop out of school. So with the large number of children dropping out of school, the level of human resources is getting weaker. In this study using a qualitative approach using interviews, observation and documentation. The results of this study indicate that the factors that cause children to drop out of school in the Fisherman Village of Medan Belawan are due to two factors, namely external factors (inadequate economy where their income is still low, the social environment of children in Fisherman Village who participate in promiscuity, distance places to live and schools are far away, and educational facilities are not yet complete) and internal (this condition includes inadequate nutrition or health factors for the children of Kampung Nelayan due to an unsanitary environment, lack of motivation for schooling, and lack of encouragement from the family environment and the environment in which he is located which makes him mentally not to go to school. As for the efforts to handle these school dropouts through the establishment of Learning Houses, Floating Libraries, and equality programs, namely the package A, package B and C programs.